Optimizing Container Delivery Services at Nilam Container Terminal: A Lean Services Approach Utilizing VALSAT Framework - Wurjaningrum, Febriana; Nurrahmani, Rania Divia (Universitas Airlangga, 2025)
The present research explores the optimization of container delivery processes at Terminal Peti Kemas Nilam using a Lean Services approach, addressing increased competition and customer expectations in the logistics supply chain by reducing waste during loading and unloading. Employing qualitative methods, including observations, questionnaires, interviews, and document analyses, the study utilized the VALSAT tool to identify waste and categorize activities into value-added (VA) and non-value-added (NVA). The analysis identified 12 activities, nine VA and three NVA, and key wastes such as waiting, unnecessary inventory, and defects. A fishbone diagram was employed to analyze root causes and guide improvement proposals, providing a framework for enhancing efficiency and service delivery in the logistics sector.